The crystal structure of 1-methyl-3-(N-methylnitrous amide–N-methylene) imidazolidine-2,4,5-trione - Xiaolin Wei; Jianhui Zhou; Jinjun Geng; Zhiwei Wen; Manyi Qu; Xiaoting Hou; Ruiqin Li; Rui Feng; Lukui Zhao; Pengbao Lian; Jianlong Wang (Zeitschrift für Kristallographie - New Crystal Structures)
C6H8O4N4, orthorhombic, Pna21 (no. 33), a = 6.5487(4) Å, b = 17.5223(9) Å, c = 7.5728(4) Å, V = 868.97(8) Å3, Z = 4, Rgt(F) = 0.0740, wRref (F2) = 0.0761, T = 106.0 K.